“Efeito do óleo essencial da citrus reticulata em portadores do distúrbio do sono do tipo insônia, no contexto da pandemia Covid-19. um ensaio experimental” - Soares, Josemar dos Santos (2021)
Insomnia is one of the most common sleep disorders, being considered a global public health issue, where it is estimated that it affects 33 to 50% of the adult population. Sleep is a fundamental biological function in the consolidation of brain protein regulation, cell repair, energy conservation, memory consolidation and learning. This research aimed to evaluate in volunteers the benefit of aromatherapy with the essential oil (EO) Citrus reticulata (Cr) by inhaled in the sleep disorder insomnia type during the SARs Covid 19 Pandemic. This is a cross-sectional, descriptive study, qualitative and quantitative, with application of an electronic form (EForm) to obtain the following information: sociodemographic characteristics, sleep information, ENT assessment, Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), Functional Outcomes of Sleep Questionnaire (FOSQ-30), Insomnia Severity Index (ISI), Chronotyping Test (CT) and application of the Sleep Diary (SD). The research was carried out in 2 groups, where Group I, intervention, with 7 volunteers, in addition to the EForm, was submitted to an otorhinolaryngological consultation, filled in the SD (without inhalation of the EO for 14 days and with EO for another 14 days). Afterwards, they filled in the EForm again for comparative effect. However, the FOSQ-30 and the TC were excluded, as they assess long-term profiles. The Group II (65 volunteers) was submitted exclusively to the EForm to assess the quality of sleep, as well as the identification of possible beneficiaries of the use of the OE of Cr. As relevant results, we found that when comparing the SD before and after the use of the EO of Cr using the Wilcoxon test for paired and non-parametric data, highly significant differences were observed (with p<0.001) in the evaluation of hours of sleep (THE); in the mood when waking up (B); on sleep quality (C) and mood during the day (D). All these items indicate an improvement in sleep after OE treatment. The results of the IGI before and after the use of the EO were compared and there was a significant difference (Z(T)= 2.37; p= 0.02), proving to be efficient in reducing insomnia. The results of the FOSQ-30 scale, with its subscales, were compared using the Wilcoxon Test and there was a significant difference only for general productivity. The ESS and the ISI were correlated through Spearman's linear correlation coefficient (rs) in relation to hours of sleep and the perception of improvement in sleep quality, measured by the SD, before and after the use of the EO, where a correlation was demonstrated. significant negative difference between the ESS after the use of the EO (before rs= -0.20; p=0.67 and after rs= -0.93; p=0.003), suggesting that for every 10 points decreased in the ESS, get an hour's sleep. The results of aromatherapy in the treatment of insomnia-type SD and the benefits of EO of Cr in this research showed to bring a contribution in improving quality, indicating that further studies are necessary to stimulate the use of this resource in the health area.